Every smile is special: Healthy Athletes Special Smiles Program makes a difference (Nigerian Dental Journal, 2008)
A smiling face on an individual can represent someone who may be happy, thankful or witnessing something that may strike them as being funny. But a smile could also denote a person with a positive self-image and self-esteem, personal well-being, or an individual with good overall health including good dental health free from pain or infection. Everyone deserves an opportunity to smile including the 190 million people worldwide with intellectual disabilities, along with the 2.5 million Special Olympics athletes competing in sports events locally, nationally, regionally and globally who live in many countries and counting the 6,374 Nigerian athletes who competed in Nigeria Special Olympics events in 2007. Unfortunately, many Special Olympics athletes as well as other individuals with intellectual disabilities are unable to access needed and often medically necessary dental care. This unmet care can cause significant oral pain and infection of both their dentition and supporting soft tissues which, if left untreated could result in considerable morbidity or death. The Special Olympics Special Smiles Program (SOSS) is trying to change worldwide the recognized inadequate access to comprehensive dental care for people with intellectual disabilities by providing educational and training programs for dentists, dental hygienists, dental students, dental hygiene students, dental educators, community leaders and government officials.